UPAYA INDONESIA DALAM MENJADIKAN BAHASA INDONESIA SEBAGAI BAHASA INTERNASIONAL DI ASIA TENGGARA - Ade Aprilyansyah (Universitas Komputer Indonesia, 2018)
Indonesian (Bahasa) experiences development in its function and position since it is set as the national language in which Indonesia improves the function of Indonesian (Bahasa) as an international language since 2009 by Act No. 24 year of 2009 where in Indonesian (Bahasa) showed has great opportunities and prospects to become an international language in Southeast Asia, which is supported by the number of domestic and foreign speakers of Indonesian and some other aspects. Yet, to make Indonesian as an international language, Indonesian experiences obstacles coming from the country and abroad. In this study, the researcher tried to analyze what the measures of Indonesia are, what the constraints faced by Indonesia in making Indonesian (Bahasa) as an international language in Southeast Asia are, and how Indonesian (Bahasa) to be international language in Southeast Asia are. The method in this research was qualitative method. Most of the data were collected from interviews and literature and supported by the literature and website searches. The study was conducted in the Development and Language Improvement Department, the Ministry of Education and Culture of Indonesia and Indonesian Institute of Sciences The result showed that Indonesian (Bahasa) has great opportunities and prospects to become an international language in Southeast Asia, which is supported by the number of domestic and foreign speakers of Indonesian and some other aspects. Yet, to make Indonesian as an international language, Indonesian experiences obstacles coming from the country and abroad.